Correlation and Regression Analysis of Tourism Development in the Republic of Tatarstan - V. A. Rubtsov; M. V. Rozhko; J. P. Alekseeva; A. Yu. Talibova (Researchparks Publishing, 2022)
In recent years, much attention has been paid to the development of domestic tourism, as this industry has a positive impact on the national and regional economy. The Republic of Tatarstan has not only rich natural, cultural and historical resources, which primarily attract tourists, but also a developed transport and tourist infrastructure. However, some indicators do not have a greater impact on the development of the industry. This article discusses the factors that influence the added value that is created directly in tourism. For analysis, 21 indicators were selected and, using correlation-regression analysis, factors were identified that have a significant impact on the development of the tourism industry in the Republic of Tatarstan.